"Social affiliation and its relation with compliance for Iraqi expatriates students" (Journal Of Educational and Psychological Researches, 2016)
Individual cannot live alone due to to his need for others to facilitate His supplies for living, thus social affiliation is considered one of the most important psychological, social needs in individuals life through his willing to affiliate to others whether they were friends ,family, colleague , or even home to reach some degree of  psychological stability.       Affiliation is a tool to search for Satiate through living with group from the same type or comply for group or to be compatible with them or even to be adherent and accept what the group agreed about of criterion.         Compliance is considered one of the personal variables that is used by individual to for psychological compatibility ,staying away from anxiety and tension sources through disclaiming of personal judgments against external stresses which makes the individual agree with others to stay away from rejection of community and being accepted from others.This research aims to:1-measuring social affiliation for Iraqi expatriates students.2-studying differences in social affiliation for  Iraqi expatriates students  according to gender(male-female).3-comparison of social affiliation with non expatriate students.4-measuring compliance for Iraqi expatriates students.5-studying differences in compliance for Iraqi expatriates students according to gender(male-female).6- comparison of compliance for Iraqi expatriates students with others of non expatriates students.7-studying the relation between social affiliation and compliance for Iraqi expatriates students.          This reseach aims to application of social affiliation and compliance scale on sample of (50) Iraqi expatriates students were chosen spontinuousley from cardf university in england and (50) student chosen spontinuously from baghdad university .It was found that:• Iraqi expatriates students have social affiliation.• There is no differences in statically significance in social affiliation for Iraqi expatriates students according to gender(male-female).• There is differences in statically significance in social affiliation for Iraqi expatriates students in comparison with non expatriate students.• Samle have compliance.• There is no differences in statically significance in compliance for Iraqi expatriates students according to gender(male-female).• There is  differences in statically significance in compliance for Iraqi expatriates students in comparison with non expatriate students.